ADDITIONAL NOTE ON CULLENIA CEYLANICA K. Schum. (Bombac) - A. J. G. H. KOSTERMANS (REINWARDTIA, 1958)
Cullenia excelsa Wight in Pearson & Brown, Commerc. Timb. India 1: 141, t. 51 1932; Foxworthy in Philipp. J. Sci. Bot. 4: 500. 1909; Trotter, Common Comm. Timb. India 65. 1901. Foxworthy in Philip. J. Sci. Bot. 4: 500. 1909. Fruit collected in January 1958 from the tree cultivated in the Bogor. Botanical Garden (no. XVI H. 13) enables me to correct and emendate the description published in "Communication of the Forest Research Institute, Bogor" no. 51 (1956) and in Reinwardtia 4 : 69.1956. The ripe fruit are dirty green outside, they open on the branches and the seed falls out immediately. Each fruit contains from one to 5 seeds, the common number, however, is one, the others do not develop; the fruit becomes pseudo-unilocular. The chestnut brown seeds are completely enveloped by a lightbrown, somewhat glassy, slightly juicy and hardly sweet, furrowed aril of 2-4 mm thickness; the apical part of the aril is more or less fimbriate. Figs. 38, 39.